Brexit and the British Constitution: Reflections on the Last Three years and the Next Fifty. Issue 1 (9th March 2020) - Sumption, Jonathan
Abstract: The decision to leave the EU provoked the biggest constitutional crisis of recent British history. The referendum—a device for circumventing the parliamentary process—was followed by conflict between a minority government and a majority of MPs unwilling to leave the EU without satisfactory alternative arrangements. The courts, drawn into this conflict, upheld conventions that sustain the authority of Parliament and restrain the despotic power of ministers. The reaction of members of the current government was to take disreputable and anti‐democratic positions against both the Speaker of the House of Commons and the courts. They now have a sufficient majority in Parliament to resume adherence to constitutional conventions and restore a political culture of debate and tolerance, but they show little sign of doing so, and there is a risk that they will do irreparable damage to the political culture that underpins democracy.